1999
DOI: 10.1002/etc.5620180533
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of trifluoroacetate to aquatic organisms

Abstract: Abstract-As a result of the atmospheric degradation of several hydrofluorocarbons and hydrochlorofluorocarbons, trifluoroacetate (TFA) will be formed. Through precipitation, TFA will enter aquatic ecosystems. To evaluate the impact on the aquatic environment, an aquatic toxicity testing program was carried out with sodium trifluoroacetate (NaTFA). During acute toxicity tests, no effects of NaTFA on water fleas (Daphnia magna) and zebra fish (Danio rerio) were found at a concentration of 1,200 mg/L. A 7-d study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 4 publications
1
27
1
Order By: Relevance
“…Previous results displayed that TFA was of mildly phytotoxic (Berends et al, 1999;Boutonnet et al, 1999). Although the observed TFA levels in aqueous environment were all below the safety level of 0.10 mg L −1 (Berends et al, 1999), high levels have been reported as early as in 1990s. For instance, TFA concentrations were reported as high as 40,900 ng L −1 in Pyramid Lake of the United States (Zehavi and Seiber, 1996); and the levels beyond 1000 ng L −1 were also recorded in rainwater around the world (Frank et al, 1995;Wujcik et al, 1998;Von Sydow et al, 2000;Berg et al, 2000;Scott et al, 2006).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Previous results displayed that TFA was of mildly phytotoxic (Berends et al, 1999;Boutonnet et al, 1999). Although the observed TFA levels in aqueous environment were all below the safety level of 0.10 mg L −1 (Berends et al, 1999), high levels have been reported as early as in 1990s. For instance, TFA concentrations were reported as high as 40,900 ng L −1 in Pyramid Lake of the United States (Zehavi and Seiber, 1996); and the levels beyond 1000 ng L −1 were also recorded in rainwater around the world (Frank et al, 1995;Wujcik et al, 1998;Von Sydow et al, 2000;Berg et al, 2000;Scott et al, 2006).…”
Section: Introductionmentioning
confidence: 89%
“…The persistence and water solubility of TFA make it potentially accumulate in some aquatic ecosystems where TFA may concentrate through water evaporation, especially in landlocked lakes (Tromp et al, 1995;Cahill et al, 2001;Wu and Chau, 2006), or in some hydrometeors, particularly in fog (Römpp et al, 2001). Previous results displayed that TFA was of mildly phytotoxic (Berends et al, 1999;Boutonnet et al, 1999). Although the observed TFA levels in aqueous environment were all below the safety level of 0.10 mg L −1 (Berends et al, 1999), high levels have been reported as early as in 1990s.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is not known whether the observed peak values arose from other sources of TFA, such as fluorinated polymers [Jordan and Frank, 1999] or fluorinated pesticides [Ellis and Mabury, 2000], or from a fast formation of TFA due to high HFC/HCFC and hydroxyl radical concentrations. Berends et al [1999] determined TFA toxicity levels for various aquatic organisms, including concentrations that had no observable effect on an organism. The most sensitive organism tested by Berends et al was the freshwater alga Raphidocelis subcapitata, with no observed effects at TFA concentrations of 100 μg L −1 .…”
Section: Tfa Rainwater Concentrationmentioning
confidence: 99%
“…Flammability is important because many industrial facilities are not equipped with safely handle flammable hydrocarbons. In addition, hydrocarbon containing an aromatic hydrocarbon, such as benzene, toluene, and xylene are being regulated due to its high toxicity on human body and environmental pollution [4,5]. Therefore, development of new environmentally acceptable cleaning agent would be highly desirable.…”
Section: Introductionmentioning
confidence: 99%